Two new species of Barssia from China - Xu, Yu-Yan; Guo, Li-Jie; Li, Ting; Fan, Li (Phytotaxa, 2018)
Two new truffle species Barssia guozigouensis and B. luyashanensis are described and illustrated from North China based on morphological and molecular evidences. Morphologically, B. guozigouensis is diagnosed by its distinctly warty ascomata and solid gleba with small and irregular chambers, and B. luyashanensis is by its red brown ascomata with fine warts and gleba without chambers. Molecular phylogenetic analyses based on the ribosomal internal transcribed spacer region and 28S large subunit nrDNA supported the placement of the new species.